Upgrading palm biodiesel properties via catalyst‐free partial hydrogenation using needle‐plate dielectric barrier discharge plasma torch. (11th April 2022) - Kamjam, Manita; Wongsawaeng, Doonyapong; Ngaosuwan, Kanokwan; Kiatkittipong, Worapon; Hosemann, Peter; Assabumrungrat, Suttichai
Summary: A catalyst‐free and ambient condition dielectric barrier discharge (DBD) plasma torch has been used to efficaciously synthesize partially hydrogenated fatty acid methyl ester (H‐FAME) obtained from refined palm oil. The electrode configuration was a needle‐to‐plate type. The effects of power, H2 flow rate, discharge gap, process temperature and reaction duration on H‐FAME compositions and properties were examined. For 1 hour of reaction time, the optimal condition was 100 W input power, 1.0 L/min H2 flow rate, 1.0 cm discharge gap and 90°C reaction temperature. Under this condition, the H‐FAME contained saturated FAMEs of 56.8% and unsaturated FAMEs of 43.1%, compared to saturated FAMEs of 48.8% and unsaturated FAMEs of 51.0% in the feed FAME. After 1 hour of treatment, the oxidation stability increased by 10.7 hours (from 12.8 to 23.5 hours), while the cloud point increased from 13.5 to 16.0°C. A reduction rate of iodine value was 13.4%/h (reduction from 50.6 to 43.8). The trans ‐fatty acid formation was not detected in the palm H‐FAME. Partial hydrogenation through the DBD plasma torch without using artificial antioxidants or metal catalysts is an environment‐friendly and potentially alternative approach, which can substitute conventional catalytic hydrogenation of FAME for enhancing the oxidation stability of biodiesel. Abstract : Optimal condition: 100 W input power, 1.0 L/min H2 flow rate, 1.0 cm discharge gap, 90°C reaction temperature, 1 hour of treatment time. A catalyst‐free and ambient condition dielectric barrier discharge plasma torch has been used to efficaciously synthesize partially hydrogenated fatty acid methyl ester (H‐FAME) obtained from refined palm oil. Under optimal condition, the H‐FAME contained saturated FAMEs of 56.8% and unsaturated FAMEs of 43.1%, compared to saturated FAMEs of 48.8% and unsaturated FAMEs of 51.0% in the feed FAME. After 1 hour of treatment, the oxidation stability increased by 10.7 hour (from 12.8 to 23.5 hour). No trans ‐fatty acid formation was detected in the palm H‐FAME.